Deconvolving the pre-Himalayan Indian margin – Tales of crustal growth and destruction - Spencer, Christopher; Dyck, B.; Mottram, C.; Roberts, N.; Yao, Weihua; Martin, E. (Elsevier, 2018)
The metamorphic core of the Himalaya is composed of Indian cratonic rocks with two distinct crustal affinities that are defined by radiogenic isotopic geochemistry and detrital zircon age spectra. One is derived predominantly from the Paleoproterozoic and Archean rocks of the Indian cratonic interior and is either represented as metamorphosed sedimentary rocks of the Lesser Himalayan Sequence (LHS) or as slices of the distal cratonic margin. The other is the Greater Himalayan Sequence (GHS) whose provenance is less clear and has an enigmatic affinity. Here we present new detrital zircon Hf analyses from LHS and GHS samples spanning over 1000 km along the orogen that respectively show a striking similarity in age spectra and Hf isotope ratios. Within the GHS, the zircon age populations at 2800–2500 Ma, 1800 Ma, 1000 Ma and 500 Ma can be ascribed to various Gondwanan source regions; however, a pervasive and dominant Tonianage population (~860–800 Ma) with a variably enriched radiogenic Hf isotope signature (eHf = 10 to -20) has not been identified from Gondwana or peripheral accreted terranes. We suggest this detrital zircon age population was derived from a crustal province that was subsequently removed by tectonic erosion. Substantial geologic evidence exists from previous studies across the Himalaya supporting the Cambro-Ordovician Kurgiakh Orogeny. We propose the tectonic removal of Tonian lithosphere occurred prior to or during this Cambro-Ordovician episode of orogenesis in a similar scenario as is seen in the modern Andean and Indonesian orogenies, wherein tectonic processes have removed significant portions of the continental lithosphere in a relatively short amount of time. This model described herein of the pre-Himalayan northern margin of Greater India highlights the paucity of the geologic record associated with the growth of continental crust. Although the continental crust is the archive of Earth history, it is vital to recognize the ways in which preservation bias and destruction of continental crust informs geologic models.